Disaster Education Supported by Infographics for Students with Mild Intellectual Disabilities (Third Sector Social Economic Review, 2026)
The primary objective of the study is to determine the effectiveness of infographic-supported instruction on the acquisition of disaster education skills by students with mild intellectual disabilities and to examine the sustainability of the acquired skills. The scope of the study is limited to skills related to earthquake preparedness, demonstrating appropriate behavior during an earthquake, and safe evacuation processes after an earthquake. The research was conducted using a multiple-tracking design between subjects from single-subject research models. The study group consisted of three 15-year-old students diagnosed with mild intellectual disabilities who attended a special education class during the 2024 - 2025 academic year. Infographic materials developed by the researcher were used in the teaching process. Data were collected at baseline, during instruction, and in follow-up and generalization sessions. Visual analysis, non-overlapping data percentage, and Tau-U methods were used for analysis. The findings revealed that infographic-supported instruction was 100% effective in imparting the targeted disaster education skills to all participants. Furthermore, it was determined that participants retained the skills they acquired at a high level after instruction and were able to successfully generalize them to different environments, individuals, or materials. It is recommended that infographics be used as an effective teaching tool in disaster education for individuals with special needs.
Keywords: Disaster education; intellectual disability; infographic; single-subject research; earthquake